Green Finance Post-Pandemic Restructuring: Mini-Overview and Approaches to Modeling Links - Igor K. KLIOUTCHNIKOV; Oleg. I. KLIUCHNIKOV; Olga A. MOLCHANOVA (Communications of International Proceedings, 2020)
Green finance is an important area of ​​tackling environmental threats, especially those associated with climate change. The Covid-19 outbreak has drawn additional attention to green finance as an economic mechanism for creating healthy living environments. The article examines the impact of COVID-19 on the financial industry, the involvement of green finance in the economic recovery after the pandemic, towards taking into account the Paris Agreement to reduce greenhouse gas emissions and improve sustainability. The authors put forward a provision on the presence of causal links between two concepts: "green" finance and "green" economy. The article substantiates the position that the global pandemic will have a long-term impact on the attitudes of investors, governments, and the public towards financing measures to protect the environment and prevent climate change. The three-agent model proposed in the article makes it possible to analyze the behavior of green finance participants. By simulating their behavior, the mechanism of adaptation of both the system and agents to internal and external pressure is analyzed in order to preserve their functionality and increase the performance and efficiency of green financing.
Keywords: Green Finance; Green Bonds; Pandemic; Climate Change; Three-Agent Model.